Effects of Work Environments and Occupational Fatigue on Care Left Undone in Rotating Shift Nurses. Issue 1 (18th November 2020) - Min, Ari; Kim, Young Man; Yoon, Yea Seul; Hong, Hye Chong; Kang, Minkyung; Scott, Linda D.
Abstract: Purpose: This study aimed to examine the effects of work environments and occupational fatigue on care left undone in rotating shift nurses, and to identify the indirect (mediation) effect of work environments on care left undone through nurses' occupational fatigue in South Korean acute care hospitals. Design: This study employed a cross‐sectional design using an online survey to collect data from 488 rotating shift nurses of acute care hospitals in Korea between November and December 2018. Methods: A mobile schedule management application for shift nurses was used to advertise the study and to send a link to the online survey. The survey included questions on the nurses' work environment characteristics, care left undone activities, and the Korean version of the Occupational Fatigue Exhaustion/Recovery scale. Poisson regression was used to explore the relationships among work environments, occupational fatigue, and care left undone. Hayes' Model 4 and a bootstrapping analysis were used to identify the mediating effect of occupational fatigue on the relationship between work environments and care left undone. Findings: The average number of tasks left undone was 3.45 ( SD = 2.19). The higher the acute and chronic fatigue levels noted among nurses, the higher were the occurrences of care left undone. Conversely, the higher the intershift recovery level, the lower were the occurrences of care left undone. The results showed a positive relationship between care left undone and overtime hours and the number of patients per nurse. Moreover, nurses' occupational fatigue mediated the relationship between work environments and care left undone. Night shifts per month and the number of consecutive days off had an indirect effect on care left undone through occupational fatigue. Conclusions: High levels of occupational fatigue and poor intershift recovery among nurses can lead to care left undone. Nurses' occupational fatigue mediates the effect of work environment on care left undone. Clinical Relevance: It is crucial for healthcare administrators and leaders to develop policies and mandatory regulations to facilitate better working conditions for nurses, consequently reducing their occupational fatigue and decreasing the occurrence of care left undone in acute care hospitals.